Halal tourism research bibliometric analysis in Scopus, ProQuest and Ebscohost / Mohd Nasir Ismail … [et al.] - Ismail, Mohd Nasir; Ismail@Ahmad, Muslim; Othman, Roslina; Ismail, Mohd Saufi (Academy of Contemporary Islamic Studies (ACIS), Universiti Teknologi MARA (UiTM), 2019)
With the emerging and increasing interest toward halal product and services, a variety of halal based research can be found in online databases. Halal tourism in research is a quite recent topics in journal articles. Halal tourism subtopics has evolved into many subtopics such as halal culinary, halal destination, halal friendly hotel, halal lodging and halal tourism supply chain. Therefore, this paper aims to analyse, visualize and discover the subject relation made in the topic of halal tourism using co-occurrence words bibliometric analysis. Data are citations from Scopus, ProQuest and Ebscohost databases using ‘halal tourism’ as keyword. The data corpus are set for research articles in English and the date range set for 1987 to 2019. Total data collection is 383 citations. Data were analysed using Scopus analyzer and VOSviewer version 1.6.10. Findings show that Scopus papers and retrieval is better in term of quality and more representative of the current research direction. Scopus search engine also provides reliable and credible result. The primary clusters in halal tourism research concentrate on research contexts, concept, halal industry and religion research. Future research should measure the data retrieval, precision and recall to verify findings in this halal tourism research.